EEG based driver cognitive distraction assessment - Almahasneh, H.S. (IEEE Computer Society, 2014)
The assessment of a drivers' cognitive distraction during driving is a challenging topic in research community. This paper states the ongoing research assessing driver's cognitive distraction using simulated driving. The driver's cognitive distraction detection is based on the analysis of EEG signal. A new analysis method based on Singular Value Decomposition (SVD) is introduced for the extraction of feature from the Electroencephalogram (EEG) signals. Hence, the results obtained consist in high accurate detection of the driver's cognitive state. Â© 2014 IEEE.